Digital Forensics: Techniques and Tools for Cybercrime Investigations (Global Journal of Computer Science and Technology, 2023)
Digital forensics is a crucial aspect of modern-day investigations particularly those involving cyber crimes With the increasing prevalence of digital devices the amount of electronic evidence available for investigation has also grown significantly Therefore it is essential to have the necessary techniques and tools to extract and analyse digital evidence accurately and efficiently This paper aims to provide an overview of digital forensics and highlight some of the most popular techniques and tools used in the field
Keywords: digital evidence; cybercrime; computer crimes; electronic fraud; recovery and preservation of electronic data